Palmitoylated Proteins on AML-Derived Extracellular Vesicles Promote Myeloid-Derived Suppressor Cell Differentiation via TLR2/Akt/mTOR Signaling - Tohumeken, Sehmus; Böttcher, Martin; Stoll, Andrej; Loschinski, Romy; Panagiotidis, Konstantinos; Braun, Martina; Saul, Domenica; Baur, Andreas; Bruns, Heiko; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios; et al. (Cancer Research, 2020)
Acute myeloid leukemia (AML) represents the most common acute leukemia among adults. Despite recent progress in diagnosis and treatment, long-term outcome remains unsatisfactory. The success of allogeneic stem cell transplantation underscores the immunoresponsive nature of AML, creating the basis for further exploiting immunotherapies. However, emerging evidence suggests that AML, similar to other malignant entities, employs a variety of mechanisms to evade immunosurveillance. In light of this, T-cell inhibitory myeloid-derived suppressor cells (MDSC) are gaining interest as key facilitators of immunoescape. Accumulation of CD14(+) HLA-DRlow monocyticMDSCs has been described in newly diagnosed AML patients, and deciphering the underlying mechanisms could help to improve anti-AML immunity. Here, we report that conventional monocytes readily takeup AML-derived extracellular vesicles (EV) and subsequently undergo MDSC differentiation. They acquired an CD14(+)HLA-DRlow phenotype, expressed the immunomodulatory indoleamine-2,3-dioxygenase, and upregulated expression of genes characteristic for MDSCs, such as S100A8/9 and cEBP beta. The Akt/mTOR pathway played a critical role in the AML-EV-induced phenotypical and functional transition of monocytes. Generated MDSCs displayed a glycolytic switch, which rendered them more susceptible toward glycolytic inhibitors. Furthermore, palmitoylated proteins on the AML-EV surface activated Toll-like receptor 2 as the initiating event of Akt/mTOR-dependent induction of MDSC. Therefore, targeting protein palmitoylation in AML blasts could block MDSC accumulation to improve immune responses.
CRIS-Team WoS Importer:2020-09-25